Comprehension and Hemispheric Processing of Irony in Schizophrenia - Saban-Bezalel, Ronit; Mashal, Nira (Frontiers in Psychology, 2017)
Studies focusing on the comprehension of figurative language among schizophrenia patients (SZ) reveal their difficulties comprehending such language and their tendency to interpret it literally. The present study investigated hemispheric processing and comprehension of irony in 16 SZ patients and 18 typically developing (TD) adults. Two experimental tasks were used: an online divided visual field experiment and an offline irony questionnaire. The results show an atypical reversal of hemispheric processing of irony in SZ patients as compared to TD adults. While the TD group demonstrated a right hemisphere advantage in processing irony, SZ patients demonstrated a left hemisphere advantage. Greater comprehension of irony was associated with decreased negative symptoms. In addition, under conditions that not involving a time restriction, the SZ patients’ performance improved. Our findings reinforce those of previous studies suggesting that brain lateralization is atypical in SZ patients.